"Vozes negras" na história da educação : racismo, educação e movimento negro no Espírito Santo (1978-2002) - Forde, Gustavo Henrique Araújo (2016)
This research investigates the historical constitution and the meanings attributed to education by capixaba black movement interrogating the fonts based on the following issues: How education constitutes the central agenda of this movement? How education was incorporated on central agenda of Espírito Santo black movement? What were the uses and meanings attributed to education by the entire movement? How the black militancy has moved and mobilized its space-time to combat racism in education? How the category “black” was conceived on the political agenda of the black movement? What implications the black movement has produced in school education? It is a historiographical practice sustained by the inexhaustibility and the plurality of sources, as well as the evidential and intercrossed reading of the documents produced and the force relations of questioning inherent to production contexts of the sources consulted. The investigated period (between 1978 and 2002) covered the phase of (re) organization of the black movement in the Espírito Santo and the year that preceded the enactment of Law nº 10639/2003 about the mandatory teaching of the history and african-brazilian and african culture in official establishments of education in Brazil. As sources were used the narratives obtained by means of interviews with black militants, reports and governmental guidelines, publications in newspapers, capixaba periodicals, photos and documents produced by black organizations. At the intersection of the Espírito Santo Education history with the history of Capixaba Black Movement, the “black voices” problematized education, didactics, curriculum, teaching materials and the training of teachers to the extent that they attributed meanings and elected to school education as a main field of political and cultural affirmation and socioeconomic rise of the black population, beyond the access and permanence of this population into the education system. On the other hand it was observed that the journey of the black militancy in the education field occurred interlaced with the practice in which “is not enough to include the curriculum content”; it is necessary also “transform the education”. In this process of transformation, discovery, identity belonging and collective historical commitment emerge as the main categories in the process of assigning meanings to educational practice guided by the Black Consciousness